Interpretation Methods in Islamic Boarding Schools: The Case of AMBS Garut and al-Kamil Tangerang - Fathurrohman, Asep Ahmad; Prasetyo, Ridwan Eko; Khalaf, Zaben Azeez (Taqaddumi: Journal of Quran and Hadith Studies, 2025)
This study is motivated by the limited research on the specific methodologies employed in tafsir (Qur'anic interpretation) education within pesantren (Islamic boarding schools), despite its significant impact on shaping religious understanding and practice. The study aims to analyze and compare the tafsir learning and teaching methodologies at Al-Mashduqi Boarding School (AMBS) in Garut and Pesantren Al-Kamil in Tangerang. The research adopts a qualitative design, with data collected through interviews, observations, and document analysis at both pesantren. Data was analyzed through thematic analysis. The findings reveal that while both pesantren share some similarities in their approach to tafsir education, they also exhibit distinct differences in curriculum design, teaching methods, and evaluation strategies, reflecting their unique educational philosophies and goals. The study concludes that the methodologies employed are influenced by factors such as the pesantren's vision, the teachers' expertise, and the students' needs. The implications encompass practical recommendations for pesantren to enhance their tafsir education programs by incorporating diverse teaching methodologies, providing adequate resources, and addressing the challenges of teaching tafsir in the modern context. Additionally, this study identifies future research opportunities on the impact of different tafsir methodologies on students' understanding and application of the Qur'an.